CLINICAL TESTS OF PHYTOPREPARATE IN COMPLEX THERAPY OF ACUTE RESPIRATORY DISEASES - Андрей Алексеевич Вековцев; Ольга Георгиевна Позднякова; Галина Андреевна Белавина; Валерий Михайлович Позняковский (Медицина в Кузбассе, 2019)
The aim of the study – the clinical approbation of a new phytocomplex in the complex therapy of acute respiratory diseases.